On the relation between ethics and society in the sociological theory of Durkheim - González, Jorge Luis Cammarano (Universidade Estadual Paulista / UNESP, 2009)
This article discusses the thematic of the relationship between Ethics and Society in the Durkheim's sociological theoric, while expression of the new way social production: the capitalism.